2011
DOI: 10.1016/j.neuroscience.2010.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Pregnenolone sulfate increases glutamate release at neonatal climbing fiber-to-Purkinje cell synapses

Abstract: Development of cerebellar Purkinje cells (PCs) is modulated by neuroactive steroids. Developing hippocampal pyramidal neurons retrogradely release a pregnenolone sulfate (PregS)-like neurosteroid that may contribute to glutamatergic synapse stabilization. We hypothesized that PregS could exert a similar effect on developing PCs. To test this hypothesis, we performed whole-cell patch-clamp recordings from PCs in acute cerebellar vermis slices from neonatal rats. PregS induced a robust (~3,000 %) and reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Progesterone, on the other hand, has been shown to have inhibitory effects, reducing the number of dendritic spines and excitatory synapses Increased glutamate levels in the MPFC in patients with PPD AM McEwen et al (Woolley and McEwen, 1993). Animal studies have also shown both that NASs can modulate glutamatergic neurons (Zamudio-Bulcock and Valenzuela, 2011) and that Glu impacts the production of NASs (Remage-Healey et al, 2008). Considering the known interactions between female hormones, NASs and glutamatergic activity, it is therefore possible that the fluctuations of female hormones and NASs in the postpartum contribute to the increased MPFC Glu fluctuations observed in PPD women.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone, on the other hand, has been shown to have inhibitory effects, reducing the number of dendritic spines and excitatory synapses Increased glutamate levels in the MPFC in patients with PPD AM McEwen et al (Woolley and McEwen, 1993). Animal studies have also shown both that NASs can modulate glutamatergic neurons (Zamudio-Bulcock and Valenzuela, 2011) and that Glu impacts the production of NASs (Remage-Healey et al, 2008). Considering the known interactions between female hormones, NASs and glutamatergic activity, it is therefore possible that the fluctuations of female hormones and NASs in the postpartum contribute to the increased MPFC Glu fluctuations observed in PPD women.…”
Section: Discussionmentioning
confidence: 99%
“…It is activated by intracellular adenosine diphosphoribose (ADPR), hydrogen peroxide, heat, and reactive oxygen species (ROS; Nilius et al, ; Wu et al, ). Abundantly expressed in neonatal cerebellar Purkinje cells, the steroid‐sensitive TRPM3 channel is required for pregnenolone sulfate‐induced glutamate release (Zamudio‐Bulcock and Valenzuela, ; Zamudio‐Bulcock et al, ). TRPM4 and TRPM5 channels are the only two members of the TRP superfamily that are Ca 2+ ‐impermeable monovalent channels (Nilius et al, ).…”
Section: Expression and Functions Of Trp Channels In The Brainmentioning
confidence: 99%
“…In the developing cerebellum, PregS strongly and reversibly enhances glutamate release onto Purkinje cells (PCs) of neonatal rats, an effect that is independent of several PregS‐sensitive targets; namely, NMDA, glycine, α7 nicotinic acetylcholine, and σ1 receptors, as well as voltage‐gated Ca 2+ channels (Zamudio‐Bulcock and Valenzuela 2011). PregS increases glutamate release by enhancing Ca 2+ entrance into pre‐synaptic terminals via a target that is sensitive to La 3+ , a non‐selective agent that modulates a number of TRP channel subtypes and is known to block TRPM3 (Zholos 2010; Zamudio‐Bulcock and Valenzuela 2011). Based on this finding, we hypothesized that TRPM3 channels are expressed at developing glutamatergic synapses on PCs and that they mediate the PregS‐induced enhancement of glutamatergic transmission.…”
mentioning
confidence: 99%